If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + (x + 1) + 5x = 4 Reorder the terms: 2 + (1 + x) + 5x = 4 Remove parenthesis around (1 + x) 2 + 1 + x + 5x = 4 Combine like terms: 2 + 1 = 3 3 + x + 5x = 4 Combine like terms: x + 5x = 6x 3 + 6x = 4 Solving 3 + 6x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 6x = 4 + -3 Combine like terms: 3 + -3 = 0 0 + 6x = 4 + -3 6x = 4 + -3 Combine like terms: 4 + -3 = 1 6x = 1 Divide each side by '6'. x = 0.1666666667 Simplifying x = 0.1666666667
| 7(A-6)= | | 7(X+4)=4X+3 | | 3(x+12)=30 | | 4n+6-2n=2(n+6) | | 7y+3=2x | | -3(x+8)=13x+1 | | 7N-2N+3P+2P= | | -15x=240 | | 2x=7y+3 | | 2-3p=0 | | b/5-3/4=1/2 | | 3(4xy+2x^2+5x^3y)= | | 7(4x+5)= | | 0.5+3.6=4.2-1.5 | | -19x=380 | | x+25x-6y+5y-11= | | 0.96y+2.25-0.06y=7.65 | | 2.2x-13=.6x | | 2x-7y=10 | | 6(x+4)= | | 168=6(-5x-2) | | Y^2-12y=-19 | | 0.5x+0.15(70)=35.5 | | 4y=-80 | | 6=11 | | 9(v+2)-3v=2(3v+4)-9 | | v/7+8=19 | | -2.4x=42.96 | | x^8+4x^7+3x^6= | | -27x^2-15x=0 | | 9x+2(2+x)=5+9x | | 10x-10-x-21=0 |